Aberrant Gray Matter Networks in Non-comorbid Medication-Naive Patients With Major Depressive Disorder and Those With Social Anxiety Disorder - Zhao, Youjin; Niu, Running; Lei, Du; Shah, Chandan; Xiao, Yuan; Zhang, Wenjing; Chen, Ziqi; Lui, Su; Gong, Qiyong (Frontiers in Human Neuroscience, 2020)
Major depressive disorder (MDD) and social anxiety disorder (SAD) are among the most prevalent and frequently co-occurring psychiatric disorders in adults and may have, at least in part, a common etiology. However, the unique and shared neuroanatomical characteristics of the two disorders have not been fully identified. The aim of this study was to compare the topological organization of gray matter networks between noncomorbid medication-naive MDD patients and SAD patients. High-resolution T1-weighted images were acquired from 37 noncomorbid medication-naive MDD patients, 24 noncomorbid medication-naive SAD patients and 41 healthy controls. Single-subject gray matter graphs were extracted from structural MRI scans, and whole-brain neuroanatomic organization was compared across the three groups. Relationships between brain network measures and clinical characteristics were analyzed. Relative to healthy controls, both MDD and SAD patients showed global decreases in clustering coefficient, normalized clustering coefficient, and small-worldness and locally decreased nodal centralities and morphological connections in the left insular, lingual and calcarine cortices. Compared with healthy controls, SAD patients exhibited increased nodal centralities and morphological connections mainly involving the prefrontal cortex and sensorimotor network. Furthermore, compared to SAD patients, MDD patients showed increased characteristic path length, reduced global efficiency, and decreased nodal centralities and morphological connections in the right middle occipital gyrus and right postcentral gyrus. Our findings provide new evidence for shared and specific similarity-based gray matter network alterations in MDD and SAD and emphasize that the psychopathological changes in the right middle occipital gyrus and right postcentral gyrus might be different between the two disorders.